Double-pulse femtosecond laser ablation for synthesis of ultrasmall carbon nanodots. (6th January 2020) - Nguyen, Vanthan; Zhao, Na; Yan, Lihe; Zhong, Peng; Nguyen, Van Canh; Le, Phuoc Huu
Abstract: Carbon nanodots (C-dots) with ultrasmall size possessing large surface-to-volume ratio are expected to improve their performance in sensing and catalytic applications. Here, we present a simple strategy to synthesis ultrasmall C-dots using double-pulse femtosecond laser ablation in solution. The size of C-dots reaches minimum value of ∼1 nm when the delay between the pulses was approaching the electron-ion relaxation time. In this case, the mean sizes of C-dots in double-pulse ablation are even smaller than that obtained in single-pulse ablation with the same laser fluence due to the suppression of rarefaction wave by the shock wave created by the second pulse. Furthermore, abundant functional groups are created on the surface of C-dots in double-pulse ablation because of reheating the nascent ablated materials by the second pulse. These results demonstrate that the double-pulse technique is therefore an effective strategy beyond single-pulse ablation to synthesis ultrasmall C-dots with abundant surface functional groups as well as other nanoparticle for catalytic and sensing applications.